Shifts in rural planning in the US and India. Issue 3 (2nd July 2016) - Dandekar, Hemalata C.
ABSTRACT: The premise that rural planning is place specific is demonstrated in this paper by tracing the changing emphasis of rural planning in the US and India. Approaches to rural development in the two countries, particularly as pertinent to the agriculture sector, intersected following Indian independence in 1947. Indian planners drew on the experience of the US at inducing changes in agriculture based on scientific experimentation and a government-financed extension system for dissemination and adoption and developed similar systems for India. Salient aspects of rural planning in the two countries are delineated including historical settlement, modern farms, corporate farms, globalization, rural services, poverty alleviation, equity, access, and environmental, economic and social sustainability. Their two trajectories illustrate how the emphasis of rural planning in each country is shaped by the complex specificities of rural places. The current convergence in the US and India on environmental sustainability, communications systems, housing, education, job training, and areas of inequity reflect global trends in rural planning.